Eksplorasi Penggunaan Quizizz sebagai Media Pembelajaran Interaktif Menurut Siswa - Utami, Dwi Dyan (Mahira: Journal of Arabic Studies & Teaching, 2025)
In Arabic language learning, a big challenge arises which is caused by the low interest and motivation of students to learn, this happens because of the delivery of material and evaluation of learning material that is monotonous which results in students feeling bored. This study aims to explore how the use of Quizizz can increase the interactivity and effectiveness of Arabic language learning according to students. This research uses a descriptive qualitative method which is designed to explore in depth the experiences, perceptions, and meanings expressed by students towards the use of Quizizz in Arabic language learning. With data collection through three main techniques, namely observation, interviews, and documentation. The results of this study strengthen the argument that Quizizz as an interactive Arabic learning media is able to significantly increase students' interest and motivation to learn.